Keberagaman Gender di Indonesia (Analisis Wacana Pemberitaan Gender pada Suku Bugis) - Munawarah, Zikrina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Indonesia has had a diverse history of homosexuality and transgenderism for a long time. This contradicts general public knowledge, which assumes that this influence originates from the Western world. This research aims to find out more about news about gender diversity in the Bugis tribe in Indonesia. News is taken from online media Kompasiana.com and Goodnewsfromindonesia. Id, and Bbc.com. These three media were chosen because they have the same reporting theme. The method used in this research is a descriptive qualitative study using Teun A. Van Dijk's discourse analysis. This research shows that the three news items fulfill the elements of discourse as text, except for the rhetorical elements in the Kompasiana.com and Bbc.com news. The three news stories both use inductive pattern explanations. The results of the analysis found that the context of gender diversity in the Bugis tribe includes roles, behavior, thought patterns, and emotional characteristics inherent in humans. Apart from that, the news also reminded the government to pay more attention to the traditions of the Bugis tribe because the culture of Indonesian society is decadent and must continue to be preserved. Keywords: Gender; Homosexual; Diversity; Bugis Tribe